Discursive strategies and ideologies in Mohammad Al-Arefe’s speeches - Enjavinezhad, Maryam (2017)
Manipulation is the exercise of illegitimate influence and authority towards others by means of discourse, so that people believe, accept, behave, and act according to the ideologies of a manipulator and against the interest of themselves (Van Dijk, 2006a). Moreover, texts and talks are not neutral; they are ideologically loaded and discourse “plays a fundamental role in the daily expression and reproduction of ideologies” (Van Dijk, 2003b, p. 4). The objective of any critical discourse analysis (CDA) is to unravel the underlying hidden agenda which is left implicit in the discourse. Indeed, public speakers and leaders can socially reconstruct reality based on own ideologies and change the social cognition through discourse. Following a qualitative research methodology, this research analyzed the ideologies and discursive practices of Mohammad Al-Arefe’s discourse, the wellknown Saudi preacher, to unveil the ideologies in his discourse with regard to the current civil war in Syria. Van Dijk’s (2003b; 2006a) framework of semantic strategies for positive self-presentation and negative other-presentation and ‘ideological square’ model were adopted as analytical tools to explore the underlying ideologies related to ingroup and outgroup presentation at the levels of meaning, formal structures, and actions and interactions. Three of Al-Arefe’s Friday sermons delivered between 2009 and 2013 in Saudi Arabia and Egypt were selected and critically analyzed at the textual and contextual levels. The findings revealed that Al-Arefe’s discourse is indexed by strong polarization between ‘Us’ and ‘Them’ and construction of an exaggerated dichotomy that divides the social groups into the two opposing poles of ‘Good’ versus ‘Evil.’ It was revealed that positive self-presentation in Al-Arefe’s discourse is manifested through lexicalization, self-glorification, victimization, euphemism, and propaganda techniques. The negative other-presentation in his discourse is also enhanced through the discursive structures of derogation, demonization, and construction of Non-Muslim identity for the Other in order to create fear and hostility towards the Other. Furthermore, the findings showed that Al-Arefe’s discourse encourages a non-human view of the ‘Other’ and legitimize violence against them based on their faith and identity. It was also argued that Al-Arefe’s discourse is heavily emotional and is featured with hyperbolic assertions, stereotyping, appeal to angers, fallacious reasoning, and repetition of ideological themes and Quranic references which contextually makes it hard for the Muslim audience, and specifically the youth, to resist manipulation. Finally, it was concluded that Al-Arefe has taken advantage of the mood of time and the context of Syria war to promote his group’s political agenda. The findings of this study offers insights into understanding how religious figures construct hate speeches and polarization in the Muslim world context and create or activate ‘preferred mental models’ which can lead to discrimination and violent social actions of worldwide impact. Indeed, this study provides an example of the way new practices are justified, legitimized, and naturalized through looking at the radical discourses that emerged in the genre of preaching. Also, it is argued that Muslim preachers’ discourse can strongly influence the social cognition, and hence, preachers have a crucial role in reproduction of social practices, attitudes, and ideologies; they can deify or satanize a cause and direct collective actions through propaganda. Finally, it is concluded that Al-Arefe’s discourse is representative of mainstream radical and extremist discourses and such discourses should be counted as dangerous speech, since they can highly affect the safety and security of multi-ethnic societies. In sum, this study can provide help with finding solutions to the major issues that the Muslim world is facing today.